2019
DOI: 10.1126/science.aax5345
|View full text |Cite
|
Sign up to set email alerts
|

Mineralogical control on the fate of continentally derived organic matter in the ocean

Abstract: First-order relationships between organic matter content and mineral surface area have been widely reported and are implicated in stabilization and long-term preservation of organic matter. However, the nature and stability of organomineral interactions and their connection with mineralogical composition have remained uncertain. In this study, we find that continentally derived organic matter of pedogenic origin is stripped from smectite mineral surfaces upon discharge, dispersal, and sedimentation in distal o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(93 citation statements)
references
References 44 publications
1
92
0
Order By: Relevance
“…To fulfill the estimated W/R ratios (0.3-1.9) for smectite dehydration, 1.6-10 wt.% of smectite is needed. Such a mineral abundance is consistent with the measured amount of smectite in the current active and passive margin 41,[43][44][45] (1.1 to 6.2 wt.% in sediments collected by a sediment trap deployed southwestern Taiwan; 4.5 to 24.8 wt.% in sediments from the ODP 1144 and 1146).…”
Section: Unitsupporting
confidence: 83%
See 1 more Smart Citation
“…To fulfill the estimated W/R ratios (0.3-1.9) for smectite dehydration, 1.6-10 wt.% of smectite is needed. Such a mineral abundance is consistent with the measured amount of smectite in the current active and passive margin 41,[43][44][45] (1.1 to 6.2 wt.% in sediments collected by a sediment trap deployed southwestern Taiwan; 4.5 to 24.8 wt.% in sediments from the ODP 1144 and 1146).…”
Section: Unitsupporting
confidence: 83%
“…Since the transformation of smectite to illite proceeds at a temperature higher than 60 °C 8,34 and produces fluids enriched in 18 O and depleted in 2 H, smectite is considered to be the most plausible mineral candidate to account for the observed geochemical signature. As abundant smectite and mixed layer (1.1-24.8 wt.% in bulk sediments) have been found in the active margin 41 and passive margin off southwestern Taiwan 39,42 , and sediments off the Luzon Arc [43][44][45][46] (ODP, sites 1144 and 1146), smectite sourced from Taiwan orogeny and Luzon Arc volcanism and later being subducted/accreted as part of the Taiwan accretionary prism is the most likely source.…”
Section: Unitmentioning
confidence: 99%
“…Investigations have revealed the association of marine OM with lithogenic minerals (Keil et al, 1997;Kennedy and Wagner, 2011), which is also observed in the sinking particles of the South China Sea, which impart a strong effect on 14 C contents of sedimentary OC (Blattmann et al, 2018). The systematic radiocarbonscapes with contrasting modern and ancient forms of sedimentary OM (see insert in Figure 1D), representing marine and petrogenic OM forms, respectively, display strong relationships with mineralogical composition, revealing mineral-specific behavior on the retention and release of terrestrial OM in the marine environment by loss-and-replacement reactions (Figure 1D; Blattmann et al, 2019). Smectite, a pedogenic mineral, loses its association with pedogenic OM and associates with marine OM in distal marine settings.…”
Section: Om-mineral Interactionsmentioning
confidence: 98%
“…The significant positive correlation between organic carbon and sedimentation rate (Supplementary Figure 3) suggests that the former is the more important, although fine-grained and reducing environments could contribute to the preservation of organic matter (Müller and Suess, 1979). Several studies have shown that OM can be stabilized and can sustain long-term preservation in marine sediments by binding with metal ions and clay minerals (Curry et al, 2007;Blattmann et al, 2019).…”
Section: Geological Framework Of the Pearl River Submarine Canyon Sedmentioning
confidence: 98%